2018
DOI: 10.1016/j.heliyon.2018.e01052
|View full text |Cite
|
Sign up to set email alerts
|

University students' usage of the internet resources for research and learning: forms of access and perceptions of utility

Abstract: Most prior studies into the utilization of internet technology for learning purposes in contemporary educational settings in developing countries has largely dealt with its impact on academic performance, communication and general educational purposes. This paper investigates the place of the internet in academic research and learning of students, through both quantitative and qualitative research approaches, using 250 undergraduate students in three selected universities within North-Eastern Nigeria. To gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 35 publications
8
63
1
5
Order By: Relevance
“…The majority of participants reported no use of additional sources of information. These findings are in contrast to those of Dogruer et al (2011) and Apuke et al (2018) which concluded that a vast amount of university students utilise additional sources of information with particular utilisation of the internet for the following:…”
Section: Theme 2: Paediatric Exposure and Training Received In The Chcontrasting
confidence: 83%
“…The majority of participants reported no use of additional sources of information. These findings are in contrast to those of Dogruer et al (2011) and Apuke et al (2018) which concluded that a vast amount of university students utilise additional sources of information with particular utilisation of the internet for the following:…”
Section: Theme 2: Paediatric Exposure and Training Received In The Chcontrasting
confidence: 83%
“…To some extent, SSA owes this rapid increase in adoption of ICT to the support rendered by donors (such as the World Bank, the Rockefeller Foundation, the Ford Foundation, and many others) that have funded projects for development and integration of web-based learning (Mkonongwa and Komba, 2018). Another notable development is the increasing use of mobile technologies (Apuke, 2018;Makinde et al, 2019). Mbarika et al (2002) concede, however, that the great strides that Africa is making towards improving internet diffusion do not tell the whole story.…”
Section: De In Africamentioning
confidence: 99%
“…(vii) Adopting strategies for lowering costs without comprising on quality (e.g. promotion of mobile and personal technology platforms that are more affordable and more popular among the target groups, (Apuke and Iyendo, 2018); use of social media for academic purposes (Apuke and Iyendo, 2017).…”
Section: Recommendations For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, blended learning requires a learning model that ensures effectiveness in online learning environments (Delialioǧlu, 2012). The advantage of online learning is easy access to search for information (Apuke & Iyendo, 2018;Luaran, Samsuri, Nadzri, & Rom, 2014). The advantages of face-to-face learning are the interaction between teachers and students and students and students.…”
Section: Introductionmentioning
confidence: 99%